The identity of Pseudecheneis sulcata (M’Clelland, 1842),with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China - Ng, Heok Hee (Zootaxa, 2006)
The identity of Pseudecheneis sulcata is clarified in this study, and the species is redescribed.  Pseudecheneis sulcata (from the Brahmaputra River drainage) can be distinguished from congeners in having a unique combination of the lack of a prominent bony spur on the anterodorsal surface of the first dorsal-fin pterygiophore, presence of a first dorsal-fin element, bifid neural spines on the complex vertebra, the neural spines of the last 2–3 preanal and first 6–7 postanal vertebrae gradually increasing in height, separate pelvic fins, a less convex snout when viewed laterally,  presence of pale spots on the body, 36–39 vertebrae, 12–14 transverse laminae on the thoracic adhesive apparatus, pelvic-fin length 21.2–28.7% SL, pectoral-fin length 121.6–156.3 % HL, length of adipose-fin base 17.8–22.7% SL, length of caudal peduncle 25.0–28.3% SL, depth of caudal peduncle 4.0–5.2% SL, and eye diameter 8.8–10.6% HL.  Pseudecheneis eddsi, new species, is described from tributaries of the Ganges River in Nepal.  Pseudecheneis eddsi can be distinguished from congeners by a unique combination of the presence of a prominent bony spur on the anterodorsal surface of the first dorsal-fin pterygiophore, presence of a first dorsal-fin element, bifid neural spines on the complex vertebra, the neural spines of the last 2–3 preanal and first 6–7 postanal vertebrae gradually increasing in height, separate pelvic fins, gently rounded snout when viewed dorsally, presence of pale spots on the body, 36–39 vertebrae, pelvic-fin length 18.0–20.9% SL, pectoral-fin length 114.9–156.0% HL, length of adipose-fin base 19.5–24.3% SL, length of caudal peduncle 25.2–27.8% SL, depth of caudal peduncle 3.5–5.3% SL, and eye diameter 9.6–12.8% HL.  Pseudecheneis stenura, new species, is also described from the Irrawaddy River drainage in southwestern China.  Pseudecheneis stenura can be distinguished from congeners by a unique combination of the presence of a prominent bony spur on the anterodorsal surface of the first dorsal-fin pterygiophore, presence of a first dorsal-fin element, bifid neural spines on the complex vertebra, the neural spines of the last 2–3 preanal and first 6–7 postanal vertebrae gradually increasing in height, separate pelvic fins, presence of pale spots on the body, 38–40 vertebrae, pelvic-fin length 20.4–24.3% SL, pectoral-fin length 160.4–196.9% HL, length of adipose-fin base 18.8–23.7% SL, length of caudal peduncle 30.3–34.5% SL, depth of caudal peduncle 2.9–3.6% SL, and eye diameter 9.2–12.8% HL.  A key to the species of Pseudecheneis is provided.